Ricardo Salvatore, Wandering paysanos: state order and subaltern experience in Buenos Aires during the Rosas era, Durham, North Carolina, Duke University Press, 2003, 804 páginas - Myers, Jorge (Universidad Nacional de Quilmes, 2004)
Fil: Myers, Jorge. Universidad Nacional de Quilmes; Argentina.